Differences in Cardiac Output and Aerobic Capacity Between Sexes Are Explained by Blood Volume and Oxygen Carrying Capacity - Diaz-Canestro, Candela; Pentz, Brandon; Sehgal, Arshia; Montero, David (Frontiers in Physiology, 2022)
Whether average sex differences in cardiorespiratory fitness can be mainly explained by blood inequalities in the healthy circulatory system remains unresolved. This study evaluated the contribution of blood volume (BV) and oxygen (O2) carrying capacity to the sex gap in cardiac and aerobic capacities in healthy young individuals. Healthy young women and men (n=28, age range=20-43 yr) were matched by age and physical activity. Echocardiography, blood pressures and O2 uptake were measured during incremental exercise. Left ventricular end-diastolic volume (LVEDV), stroke volume (SV), cardiac output (Q), peak O2 uptake (VO2peak) and BV were assessed with precise methods. The test was repeated in men after blood withdrawal and reduction of O2 carrying capacity, reaching women’s levels. Before blood normalization, exercise cardiac volumes and output (LVEDV, SV, Q) adjusted by body size and VO2peak (42±9 vs. 50±11 ml∙min-1∙kg-1, P<0.05) were lower in women relative to men. Blood normalization abolished sex differences in cardiac volumes and output during exercise (P≥0.100). Likewise, VO2peak was similar between women and men after blood normalization (42±9 vs. 40±8 ml∙min-1∙kg-1, P=0.416). In conclusion, sex differences in cardiac output and aerobic capacity are not present in experimental conditions matching BV and O2 carrying capacity between healthy young women and men.